2019
DOI: 10.5653/cerm.2019.00136
|View full text |Cite
|
Sign up to set email alerts
|

The impact of two doses of coenzyme Q10 on semen parameters and antioxidant status in men with idiopathic oligoasthenoteratozoospermia

Abstract: Objective: Oxidative stress contributes to male infertility, and antioxidants have been recommended for treating idiopathic oligoasthenoteratozoospermia (OAT). There is, however, a lack of agreement on the type, dosing, and use of individual antioxidants or combinations thereof. The purpose of this study was to compare the effects of two doses of coenzyme Q10 (CoQ10) on semen parameters and antioxidant status in men with idiopathic OAT. Methods: In this prospective study, patients with idiopathic OAT received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 35 publications
(56 reference statements)
2
41
1
Order By: Relevance
“…Among the studies included in this meta‐analysis, Safarinejad (2009) used the highest dose (300 mg) for the longest duration (26 weeks), which incidentally also showed the most significant improvement in most of the parameters. Recent investigations suggested that a higher daily dose of CoQ10 (400–600 mg) gives better results in comparison with 200 mg dose (Alahmar, 2019). Furthermore, it is seen that the noticeable improvement is seen after a minimum of 3 months of treatment (Alahmar, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the studies included in this meta‐analysis, Safarinejad (2009) used the highest dose (300 mg) for the longest duration (26 weeks), which incidentally also showed the most significant improvement in most of the parameters. Recent investigations suggested that a higher daily dose of CoQ10 (400–600 mg) gives better results in comparison with 200 mg dose (Alahmar, 2019). Furthermore, it is seen that the noticeable improvement is seen after a minimum of 3 months of treatment (Alahmar, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations suggested that a higher daily dose of CoQ10 (400–600 mg) gives better results in comparison with 200 mg dose (Alahmar, 2019). Furthermore, it is seen that the noticeable improvement is seen after a minimum of 3 months of treatment (Alahmar, 2019). Nevertheless, treatment beyond 6 months does not show further improvement (Alahmar, 2019; Safarinejad, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its reduced form, ubiquinol, is an antioxidant that protects sperm plasma membrane from lipid peroxidation [ 109 ]. In a prospective study, it was shown that treatment of CoQ10 increases sperm concentration, progressive and total sperm motility, antioxidant capacity, and SOD and CAT activity in men with idiopathic oligoasthenoteratozoospermia (OAT) [ 110 ]. At a higher dose, both semen parameters and antioxidant status were further increased, suggesting that CoQ10 may be beneficial in treating idiopathic OAT [ 110 ].…”
Section: Effects Of Aging and Oxidative Stress On Human Spermatozomentioning
confidence: 99%